2015
DOI: 10.1353/cp.2015.0040
|View full text |Cite
|
Sign up to set email alerts
|

Brave New Words: The Complexities and Possibilities of an “Indigenous” Identity in French Polynesia and New Caledonia

Abstract: In French Polynesia and New Caledonia, the “indigenous strategy” in reference to the world indigenous movement and UN indigenous rights instruments is a relatively new one in the struggle to recover sovereignty. Individuals and volunteer associations only began to explore the possibilities of this strategy in the mid-1990s, and it continues to hold a marginal place in the political field of the French territories in Oceania. This article explores how indigeneity and indigenous rights are understood and enacted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…New Caledonia-Kanaky is one out of 17 countries on the UN list of Non-Self-Governing Territories, defined by the UN Special Committee on Decolonisation (C-24) as "territories whose people have not yet attained a full measure of self-government" (UN 2021). Since the Matignon Accords in 1988 and the Nouméa Accord in 1998, however, the territory has for the most part embraced an ongoing process of decolonisation, the term used in the Nouméa Accord (Gagné 2015). There have been three referendums on political independence from France since 2018.…”
Section: Introductionmentioning
confidence: 99%
“…New Caledonia-Kanaky is one out of 17 countries on the UN list of Non-Self-Governing Territories, defined by the UN Special Committee on Decolonisation (C-24) as "territories whose people have not yet attained a full measure of self-government" (UN 2021). Since the Matignon Accords in 1988 and the Nouméa Accord in 1998, however, the territory has for the most part embraced an ongoing process of decolonisation, the term used in the Nouméa Accord (Gagné 2015). There have been three referendums on political independence from France since 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, struggles by excluded groups can involve the invention, reinvention, smudging, or affirming of versions of the past to legitimate the claims they lay in the present, to claim history for one's own group, and to render other versions inaccurate or unjust(Rabasa 2005;Hobsbawm and Ranger 2012). Processes of social mobilization may be influenced, moreover, by protection assigned to indigenous rights and self-determination by global organizations and ngo s. A case in point is the United Nations and the UN General Assembly Declaration on the Rights of Indigenous Peoples in 2007, which, together with the proliferation of social media, has both increased awareness of rights, claims of indigeneity, and influenced forms of mobilization across local, national, and global levels(Gagné 2015;Pelican 2013;Morton 2019). Still, it should be recognized that contemporary struggles for indigenous rights and the claiming of history based on global discourses and languages of rights have long roots (see Chapter 7).…”
mentioning
confidence: 99%
“…In Québec (and Canada), the United Nations approach to indigeneity and indigenous peoples was generalised and used by academics, while the notion 'autochtonie' (indigineity) caused great concern, generally speaking, among French scholars. 4 Research that we carried out in the following years on how indigeneity and indigenous rights are understood and enacted in New Caledonia and French Polynesia, two French territories in Oceania, revealed that it is not only French mainlanders who are suspicious of or uncomfortable with the notion, but that the (formerly) colonised peoples of these territories who were expected to identify with the category shared the same discomfort (Gagné 2015). Through the study of specific examples, it became clear that part of the explanation for this uneasiness lies in the fact that the 'framework' or contexts for the struggles of the indigenous peoples of the French territories in Oceania differs radically from those of other groups who have been seen as embodying the category 'indigenous peoples', such as the Amerindians and the Inuit of North America, the Māori of New Zealand, and the Aborigines of Australia.…”
mentioning
confidence: 99%
“…Although this visitor appreciated what he called a window onto an immaterial dimension or even a spiritual world that was alien to him, his use of the word 'communitarian' (communautaire) also reveals a certain unease regarding an overly culture-specific perspective in a museum openly displaying a universalist orientation. More generally, the words 'communautaire' and 'communautarisme' are used to denounce ethnic or religious isolationism or sectarianism (see Gagné 2015). In the public debate in France, 'communities' are often associated with social and political tensions.…”
mentioning
confidence: 99%